Cryptocurrency in Portfolio Management: Risk Return Optimization and Diversification Efficiency in Institutional Asset Allocation - Kurniawan, Deri Alan (Indonesian Scientific Publication, 2025)
The growing institutional interest in cryptocurrencies has prompted renewed academic exploration into their role as alternative investment assets. This study investigates the risk return characteristics and diversification potential of cryptocurrencies specifically Bitcoin and Ethereum within mixed asset portfolios. Drawing on a combination of mean variance optimization, GARCH Copula modeling, and empirical simulations, the research evaluates performance metrics across various crypto allocation levels and market conditions. The analysis incorporates dynamic rebalancing, transaction cost modeling, Monte Carlo simulations, and historical stress tests to ensure results reflect real-world portfolio dynamics and market shocks. Key findings demonstrate that small allocations of cryptocurrency (1%–3%) can enhance Sharpe ratios and extend the efficient frontier under normal market conditions. However, during periods of systemic stress such as the COVID 19 pandemic and 2022 tech selloff correlations between cryptocurrencies and equities rise significantly, reducing diversification benefits. Transaction cost thresholds also play a pivotal role; diversification benefits tend to erode when trading costs exceed 2%. Overall, cryptocurrencies can enhance portfolio performance but only within a dynamic, risk-aware framework. Their integration must account for volatility, regulatory uncertainty, and infrastructure readiness. These insights contribute to both academic debate and practical asset allocation strategies.